The Malayan emergency - Lara Ariffin; Harun Rahman; Wong, Chin Hor; Novista; AETN All Asia Networks; Perbadanan Kemajuan Filem Nasional Malaysia; Malaysia. Kementerian Penerangan Komunikasi dan Kebudayaan ([Kuala Lumpur] : AETN All Asia Networks and National Film Department Corporation Malaysia (FINAS), 2010)
In 1948, an underclared war on terror exploded in the jungles of Malaya. British and Malayan security forces a formidable guerilla army determinated to create a communist republic. They failed but by the time the war ended 12 years later, tens of thousands of people had been killed, both combatants and civillians. Yet against this terrible background, Malayans from all races and classes joined together to form a new nation independent Malaya. The Malayan Emergency was an education in fighting together the crucible independence.
Produced with the participation of Ministry of Information, Communication and Culture, Malaysia and National Film Department Corporation Malaysia (FINAS)
Executive producer, Mustazha Mustafa ; editors, Lara Ariffin, Harun Rahman
Narrator: Timothy Watson
dvd format
Keywords: Communist -- Malaysia; Malaysia -- History; Malaysia -- Politics and government; Malaysia -- Economic conditions